Establishing patterns of change in the indicators of using milk processing shops at a community territory - Tryhuba, Anatoliy; Rudynets, Mykola; Pavlikha, Nataliia; Tryhuba, Inna; Kytsyuk, Iryna; Kornelyuk, Olga; Fedorchuk-Moroz, Valentyna; Androshchuk, Igor; Skorokhod, Iryna; Seleznov, Dmytro (Eastern-European Journal of Enterprise Technologies, 2019)
An approach has been proposed to the justification of patterns in the changes of indicators related to using milk processing shops at their various parameters at a community territory, taking into account changes in production conditions. The basis of the approach is a series of experimental studies on components of production conditions, taking into consideration their characteristics in each individual community. The study implied modeling of work at processing shops. It was established that there are two periods of milk processing ‒ intensive one (from day 119 to day 301 within a calendar year) and non-intensive one (from day 1 to day 118 and from day 302 to day 365 within a calendar year) based on forecasting daily volumes of milk supplied for processing from communities’ farms over a calendar year. It is necessary to organize operation of shops in two shifts during the intensive period of milk processing, and in one shift during the non-intensive one. It was established that the laws of Weibull distribution describe daily volumes of milk processing. Their statistical characteristics during the intensive and non-intensive periods are: coefficient of variation is 0.65 and 0.62; shape parameter is 1.56 and 1.64, respectively. The confidence interval is within 509...6,995 and 46...634 liters. We carried out a study to justify regularities of change in the indicators of using milk processing shops at their various parameters at a community territory, taking into account changes in production conditions using an example of production conditions in the Brodivsky region of Lviv oblast (Ukraine). It was found that an increase in the productivity of milk processing shops from 0.5 to 20 t/day leads to the proportional decrease in specific energy consumption from 116 to 10 kW/t, specific water consumption from 10 to 0.3 m3/t and the specific demand (Nu) in human labor from 0 to 0.3 people/t in the production of various types of dairy products. We studied changing production conditions and identified trends in changes in the parameters of using milk processing shops at community territories. They underlie the determination of cost indicators. The results of this study will be useful for the identification of a configuration of projects to create milk production shops at a community territory